A Pathovar of Xanthomonas oryzae Infecting Wild Grasses Provides Insight Into the Evolution of Pathogenicity in Rice Agroecosystems - Lang, Jillian M.; Pérez-Quintero, Alvaro L.; Koebnik, Ralf; DuCharme, Elysa; Sarra, Soungalo; Doucoure, Hinda; Keita, Ibrahim; Ziegle, Janet; Jacobs, Jonathan M.; Oliva, Ricardo; Koita, Ousmane; Szurek, Boris; et al. (Frontiers in Plant Science, 2019)
Xanthomonas oryzae (Xo) are critical rice pathogens. Virulent lineages from Africa and Asia and less virulent strains from the US have been well characterized. X. campestris pv. leersiae (Xcl), first described in 1957, causes bacterial streak on the perennial grass, Leersia hexandra, and is a close relative of Xo. L. hexandra, a member of the Poaceae, is highly similar to rice phylogenetically, is globally ubiquitous around rice paddies, and is a reservoir of pathogenic Xo. We used long read, single molecule, real time (SMRT) genome sequences of five strains of Xcl from Burkina Faso, China, Mali and Uganda to determine the genetic relatedness of this organism with Xo. Novel Transcription Activator-Like Effectors (TALEs) were discovered in all five strains of Xcl. Predicted TALE target sequences were identified in the L. perrieri genome and compared to rice susceptibility gene homologs. Pathogenicity screening on L. hexandra and diverse rice cultivars confirmed that Xcl are able to colonize rice and produce weak but not progressive symptoms. Overall, based on average nucleotide identity, type III effector repertoires and disease phenotype, we propose to rename Xcl to X. oryzae pv. leersiae (Xol) and use this parallel system to improve understanding of the evolution of bacterial pathogenicity in rice agroecosystems.